The new age of sexism : how the AI revolution is reinventing misogyny / Laura Bates. - Bates, Laura, 1986- (Simon & Schuster, 2025)
Step into a world where little girls dressed up as women dance for an audience of adult men. A pornographic deepfake image or video of you exists on the internet and you just don't know it yet. Men create 'perfect' AI girlfriends who live in their pocket - customised to every last detail, only lacking the ability to say no. This isn't an image of the future. Sex robots, chatbots and the metaverse are here and spreading fast. A new wave of AI-powered technologies, with misogyny baked into their design, is putting women everywhere in danger. In 'The New Age of Sexism', Sunday Laura Bates takes the reader deep into the heart of this strange new world.